Formulation and evaluation of fast dissolving tablet of albendazole (International Current Pharmaceutical Journal, 2012)
Albendazole is broad spectrum anthelmintic use against many helminths. It is used for treatment of Threadworm, Hookworm, and Tapeworm. It has low bioavailability due to its first pass metabolism.  In the present work, fast dissolving tablet of Albendazole was design with a view to and provide a quick onset of action. The main objective of the study was to formulate fast dissolving tablets of Albendazole to achieve a better dissolution rate and further improving the bioavailability of the drug. Fast dissolving tablets prepared by direct compression and using super disintegrants in different concentration and evaluated for the pre-compression parameters. The prepared tablets were evaluated for post compressional evaluation. Among all, the formulation F3 containing 5%w/w superdisintegrant Crospovidone and 20%w/w Microcrystalline Cellulose was considered to be best formulation, which release up to 99.097% in 40 min.DOI: http://dx.doi.org/10.3329/icpj.v1i10.11848 International Current Pharmaceutical Journal 2012, 1(10): 311-316